2019
DOI: 10.1097/eja.0000000000001016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive end-expiratory pressure on gastric insufflation during induction of anaesthesia when using pressure-controlled ventilation via a face mask

Abstract: BACKGROUND Face mask ventilation (FMV) during induction of anaesthesia is associated with risk of gastric insufflation that may lead to gastric regurgitation and pulmonary aspiration. A continuous positive airway pressure (CPAP) has been shown to reduce gastric regurgitation. We therefore hypothesised that CPAP followed by FMV with positive end-expiratory pressure (PEEP) during induction of anaesthesia would reduce the risk of gastric insufflation. OBJECTIVE The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…Using gastric ultrasound to perform serial cross‐sectional areas of the gastric antrum in both the supine and right lateral decubitus positions, preliminary data involving 30 healthy fasted adults found no significant differences in gastric distension or volume of gastric secretions before or after breathing spontaneously via high‐flow nasal oxygen at 70 l.min ‐1 for 30 min . This finding is consistent with a recent study that found no gastric insufflation when pre‐oxygenation was performed with peak inspiratory pressures of up to 15 cmH 2 O . In the second abstract, the effect of pre‐oxygenation techniques on functional residual capacity were compared in 40 patients undergoing bariatric surgery randomly selected to facemask pre‐oxygenation with a PEEP of 7 cmH 2 O vs. high‐flow nasal oxygen at 50 l.min ‐1 which increased to 70 l.min ‐1 during apnoea.…”
supporting
confidence: 86%
“…Using gastric ultrasound to perform serial cross‐sectional areas of the gastric antrum in both the supine and right lateral decubitus positions, preliminary data involving 30 healthy fasted adults found no significant differences in gastric distension or volume of gastric secretions before or after breathing spontaneously via high‐flow nasal oxygen at 70 l.min ‐1 for 30 min . This finding is consistent with a recent study that found no gastric insufflation when pre‐oxygenation was performed with peak inspiratory pressures of up to 15 cmH 2 O . In the second abstract, the effect of pre‐oxygenation techniques on functional residual capacity were compared in 40 patients undergoing bariatric surgery randomly selected to facemask pre‐oxygenation with a PEEP of 7 cmH 2 O vs. high‐flow nasal oxygen at 50 l.min ‐1 which increased to 70 l.min ‐1 during apnoea.…”
supporting
confidence: 86%
“…In addition, the use of nasal CPAP can decrease the incidence of RRCs by increasing the intrapleural pressure, which would in turn increase the duration of constriction of the lower esophageal sphincter [ 10 ]. As the incidence of RRCs is significantly decreased in the nasal CPAP group, the risk of aspiration could be potentially decreased as well [ 11 ]. Therefore, the use of nasal CPAP as preferred airway management for patients with OSA can provide a consistent supply of oxygen to keep the patient’s airway open throughout the FLIP panometry procedure and thereby prevent any pharyngeal airway obstruction that otherwise leads to intraoperative movements secondary to hypercapnia-induced sympathetic activation translating into the decreased quality of the FLIP panometry results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intraoperative patient movement was not observed in any patient in the rocuronium group. As PIP increases, the risk for gastroesophageal insufflation also increases, which may increase the risk for pulmonary aspiration 28 . Although no significant difference was observed in our study, the rate of gastric insufflation was nearly three times less in the rocuronium group than in the control group (10.3% vs. 32.1%, respectively, P = 0.056).…”
Section: Discussionmentioning
confidence: 99%